2021
DOI: 10.1021/acsinfecdis.0c00580
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Deubiquitinating Enzyme Inhibitors Display in Vitro and in Vivo Activity against Malaria Parasites and Potentiate Artemisinin Action

Abstract: The ubiquitin proteasome system (UPS) is an emerging drug target in malaria due to its essential role in the parasite’s life cycle stages as well its contribution to resistance to artemisinins. Polymorphisms in the Kelch13 gene of Plasmodium falciparum are primary markers of artemisinin resistance and among other things are phenotypically characterized by an overactive UPS. Inhibitors targeting the proteasome, critical components of the UPS, display activity in malaria parasites and synergize artemisinin actio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Nonsynonymous mutations in four proteins, K13, 17,18,95 AP-2µ, 96 UBP1, 51,96,97 and coronin, 44 as well as deletions or knockdown of several others 51,76,77 have been shown to cause ART resistance in vitro. K13 mutations are responsible for ART resistance in most patients.…”
Section: K13-independent Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…Nonsynonymous mutations in four proteins, K13, 17,18,95 AP-2µ, 96 UBP1, 51,96,97 and coronin, 44 as well as deletions or knockdown of several others 51,76,77 have been shown to cause ART resistance in vitro. K13 mutations are responsible for ART resistance in most patients.…”
Section: K13-independent Resistancementioning
confidence: 99%
“…49 It has further been suggested that an elevated stress response is required as a second component in addition to reduced endocytosis to survive DHA exposure. 71 Inhibitors affecting the stress response, like deubiquitinase inhibitors and proteasome inhibitors, or increasing stress therefore synergize with ART 49,97,125 and make Plasmodium-specific proteasome inhibitors, which are also potent as monotherapy, promising candidates for new partner drugs. [126][127][128][129][130] 3.5 | Genetic background and geographic distribution…”
Section: Stress Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Experimental tractability of RMPs could also mean such mutant parasites could be assessed for transmission fitness in the absence and or presence of drug pressure. These mutant RMPs are also offering opportunities to assess the ex vivo and in vivo efficacy of antimalarial agents which can be used as combinational partners with ARTs to offset resistance (Simwela et al ., 2020 b , 2021 ).…”
Section: Applications Of Animal Models In Malariamentioning
confidence: 99%